Insight into the Thiol-yne Kinetics via a Computational Approach - ERDEM, SAFİYE; FINDIK, VOLKAN (AMER CHEMICAL SOC, 2021)
Thiol-yne reactions have drawn attention because of the click nature as well as the regular step-growth network nature of their products, despite the radical-mediated reactant. However, the factors governing the reaction pathways have not been examined using quantum chemical tools in a comprehensive manner. Thereupon, we have systematically investigated the mechanism of thiol-yne reactions, focusing on the structural influences of thiol and alkyne functionalities. The reaction kinetics, structure-reactivity relations, and E/Z diastereoselectivity of the products have been enlightened for the first cycle of the thiol-yne polymerization reaction. For this reason, a diverse set of 11 thiol-yne reactions with four thiols and eight alkynes was modeled by means of density functional theory. We performed a benchmark study and determined the M06-2X/6-31+G(d,p) level of theory as the best cost-effective methodology to model such reactions. Results reveal that spin density, the stabilities of sulfur radicals for propagation, and the stability of alkenyl intermediate radicals for the chain transfer are the determining factors of each reaction rate. Intramolecular p-p stacking interactions at transition-state structures are found to be responsible for Z diastereoselectivity.
Keywords: FREE-RADICAL POLYMERIZATION; CLICK CHEMISTRY; BENZENETHIYL RADICALS; THIOLACETIC ACID; ANTI-MARKOVNIKOV; FLASH-PHOTOLYSIS; ADDITION RATES; THIYL RADICALS; ENE; MECHANISM